Determinants of Vegetarianism and Meat Consumption Frequency in Ireland - Leahy, Eimear; Lyons, Seán; Tol, Richard S.J. (Economic & Social Studies, 2011)
Vegetarianism is increasing in the western world. This trend can be attributed to heightened health, environmental and animal welfare concerns. In this paper we investigate the factors associated with vegetarianism and pescetarianism among adults in Ireland. Using the 2007 Survey of Lifestyles, Attitudes and Nutrition (SLÁN), we use logit models to assess the relationship between vegetarianism and the socio-economic and personal characteristics of the respondents. We also analyse the factors associated with varying levels of meat and fish consumption using ordinary least squares. We find that household size, age, income and education explain meat and fish consumption; and that marital status, health indicators, and lifestyle are associated with meat and fish consumption.
Keywords: vegetarianism; meat consumption; Ireland